(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
We conduct this research in order to measure effects of inter factors such as cost of interest, operating cost, lending rate, interest revenue , etc. on a key internal factor, that is accounting net profit of the firm. This study use both quantitative analysis method with OLS regression (Eview) and with statistic analysis, and qualitative analysis including synthesis and inductive methods. The research findings tell us that in order to increase accounting net profit, the bank will better manage costs and have cost planning effectively and better manage interest cost (going down)which will drive its profitability. Besides, this study also give out recommendations for enhancing business results and operation results of a typical Vietnam bank, CTG (Vietinbank) in future and give out directions or implications for socio-economic policies.